THE INFLUENCE OF CREATIVE ACCOUNTING AND OTHER FACTORS TO DIVIDEND PAYOUT RATIO - METTA TJUNGANDI; RICKY A. MULYANA (Jurnal Bisnis dan Akuntansi, 2018)
The objective of this research is to analyze the influence of creative accounting, liquidity, size, leverage, return on equity and sales growth on dividend payout ratio. Population in this research is all listed manufacturing companies in Indonesia Stock Exchange during 2010 to 2012. Samples are obtained through purposive sampling method, in which 37 listed manufacturing companies in Indonesia Stock Exchange meet the sampling criteria resulting 111 data available are taken as sample. The result of this research shows that return on equity and sales growth have influence to dividend payout ratio. On the other hand, creative accounting, liquidity, size and leverage do not influence dividend payout ratio.